2004
DOI: 10.1159/000076950
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Tests and Thyroid Hormone Concentrations in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Objective: To evaluate the relationship between pulmonary function tests, arterial blood gases, and thyroid gland functions in patients with chronic obstructive pulmonary disease (COPD). Subjects and Methods: Thirty-two patients (mean age 64.1 ± 7.3 years, range 53–84 years) with stable COPD (mean duration of disease 11.1 ± 9.1 years, range 1–30 years) and 15 healthy control cases participated in the study. Pulmonary function, arterial blood gas, and thyroid hormone concentration were measured, and thyroid ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 8 publications
2
24
1
4
Order By: Relevance
“…1). The decreased T 3 and TSH and the increased rT 3 serum levels observed in this model of acute inflammatory lung injury are in agreement with those seen in the clinical setting of critical illness in patients with acute lung injury (ALI) and in animal models of acute illness (27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Resultssupporting
confidence: 83%
“…1). The decreased T 3 and TSH and the increased rT 3 serum levels observed in this model of acute inflammatory lung injury are in agreement with those seen in the clinical setting of critical illness in patients with acute lung injury (ALI) and in animal models of acute illness (27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Resultssupporting
confidence: 83%
“…They did not find any correlation between arterial blood gas measurement and thyroid hormone concentrations in patients with COPD. Okutan et al (12) found that level of FT3 was higher in stable COPD than control group. They reported that there was negative correlation between pulmonary function tests and PaO 2 or FT3.…”
Section: Discussionmentioning
confidence: 95%
“…Further studies are needed to verify if impaired thyroid function really increases the risk of COPD exacerbation and if proper hormonal treatment would impact the clinical outcome. Authors of other studies reported on lower spirometry parameters in patients without clinically diagnosed hypothyroidism, but with low values of thyroid hormones, that still remained within normal limits [14]. It is of note that the muscle weakness, caused by hypothyroidism, is reversible after treatment [33].…”
Section: Hypothyroidismmentioning
confidence: 94%
“…There is a growing evidence that thyroid gland function may be disturbed in COPD patients [2,5,[13][14][15][16]. Some studies show that thyroid diseases are more frequent among patients with COPD.…”
Section: Wwwjournalsviamedicaplmentioning
confidence: 99%
See 1 more Smart Citation